Gas sensing applications of multilayer graphene grown on Co-Ni/Al2O3 substrate by chemical vapour deposition - Ali M.; Ayodele B.V.; Yasin F.M.; Hamidon M.N.; Rashid S.A. (Inderscience Publishers, 2023)
Ammonia; Chemical detection; Gas detectors; Graphene; Multilayer films; Multilayers; Chemical vapour deposition; Fixed voltage; Gas sensing applications; Multilayer graphene; Saturation levels; Sensor device; Synthesised; Test chambers; Chemical vapor deposition